Device to Device Communication for Internet of Things Ecosystem: An overview - Gismalla, Mohammed Salih Mohammed; Abdullah, Mohammed Faiz Liew (International Journal of Integrated Engineering, 2017)
Device to device (D2D) communication is deemed as an emerging technology to support next-generation of cellular networks, it reduces time delay in communication, saves the energy consumption, and offer better spectrum efficiency.Â  The exchange of information between groups of D2D communication connected simultaneously under the umbrella of cellular networks is presented and called internet of things (IoT). The purpose of this paper is to investigate the D2D communication and IoT technology.Â  We present state of the art of these emerging technologies included related works and applications, in conclusion, we present the challenges and new trends of research for both technologies.